Sustainable Design and Manufacturing 2018 Proceedings of the 5th International Conference on Sustainable Design and Manufacturing (KES-SDM-18) - Dao, Dzung; Howlett, Robert J.; Setchi, Rossi; Vlacic, Ljubo (Smart Innovation, Systems and Technologies,, 2019)
This book gathers papers presented at the 5th International Conference on Sustainable Design and Manufacturing (SDM-18), held in Gold Coast, Australia in June 2018. The conference covered a wide range of topics, including: sustainable product design and service innovation, sustainable processes and technology for the manufacturing of sustainable products, sustainable manufacturing systems and enterprises, decision support for sustainability, and the study of the societal impact of sustainability including research on the circular economy. The corresponding application areas are wide and varied. The aim of cutting-edge research into sustainable design and manufacturing is to enable the manufacturing industry to grow by adopting more advanced technologies, and at the same time improve its sustainability by reducing its environmental impact. With these goals in mind, the book provides an excellent overview of the latest research and development in the area of Sustainable Design and Manufacturing.